2016
DOI: 10.1016/j.bjane.2014.08.006
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the postoperative analgesic effects of naproxen sodium and naproxen sodium-codeine phosphate for arthroscopic meniscus surgery

Abstract: The combination of naproxen sodium-codeine phosphate provided more effective analgesia than naproxen sodium and did not increase side effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…Eight studies evaluated the efficacy of pre‐emptive nonopioid pain medications (Table 2) [4, 13, 25, 28, 30, 35, 46, 47]. Seven studies examining preoperative analgesia had placebo groups and were included in the quantitative syntheses.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Eight studies evaluated the efficacy of pre‐emptive nonopioid pain medications (Table 2) [4, 13, 25, 28, 30, 35, 46, 47]. Seven studies examining preoperative analgesia had placebo groups and were included in the quantitative syntheses.…”
Section: Resultsmentioning
confidence: 99%
“…2). Bali et al [4] found that pre‐emptive naproxen and codeine reduced postoperative pain scores and rescue opioid consumption in the immediate postoperative period when compared to naproxen alone. Table 2 demonstrates the outcomes of all studies included in the review.…”
Section: Resultsmentioning
confidence: 99%
“…Several other studies have also documented the efficacy of nonopioid oral medications after arthroscopy and other orthopaedic procedures. [12][13][14][15][16][17][18][19] Gimbel et al 14 studied a variety of orthopaedic procedures and concluded that celecoxib may serve as a better option for postoperative pain control compared with hydrocodone/acetaminophen. A recent study by Pham et al 19 showed that use of oral NSAIDs (ibuprofen) and limited narcotics resulted in excellent pain relief and patient satisfaction after arthroscopic meniscectomy, which supports our current findings for limited narcotics after an arthroscopic procedure.…”
Section: Discussionmentioning
confidence: 99%
“…There is also controversy over the use of NSAIDs after orthopedic procedures, with several studies indicating that NSAIDs inhibit osteogenesis and delay bone healing. 12,13,32,33 We consider it good practice to recommend taking NSAIDs along with food and to maintain proper hydration to minimize the risk of gastrointestinal and renal complications.…”
Section: Discussionmentioning
confidence: 99%
“…They demonstrated that the naproxen sodiumecodeine combination was superior to placebo or naproxen sodium alone. In another study, Bali et al [23] compared the efficacy of preemptive 550 mg naproxen sodium and naproxen sodiumecodeine (550 mg þ 30 mg) in patients undergoing arthroscopic meniscectomy, and they also found that the combination of naproxen sodiumecodeine provided more effective analgesia and lower meperidine consumption than naproxen sodium alone. Similarly, in our study, we found that naproxen sodiumecodeine reduced the pain intensity and also reduced tramadol consumption by almost 50% compared with placebo when used as a supplemental analgesic to tramadol PCA.…”
Section: Discussionmentioning
confidence: 99%